"Social Workers Can't Be Republicans": Engaging Conservative Students in the Classroom. (2nd January 2020) - Lerner, Justin E.
ABSTRACT: Over the past 50 years, the United States has experienced the disappearance of moderate politics replaced by a more divisive political ideology. As the country has become more polarized, universities, schools of social work, and professors have increasingly leaned left. In this era of extreme political polarization, social work educators have a responsibility to create a classroom environment in which conservative students can enhance the diversity of thought in schools of social work so that all students can be more skillful social workers while helping these students understand social work values derived from the National Association of Social Workers' Code of Ethics. Using Johari's window as a theoretical framework, recommendations are provided on how to productively engage conservative students.